Effect of Notoginsenoside R1 on reparative dentin formation via regulating the function of human dental pulp stem cells - Xuan He; Dan Liang; Xinyi Zhao; Kaixin Liu; Zicheng Zhang; Meiling Li; Xuemeng Ma; Wenxia Chen; Xiaoyi Zhong (Tissue and Cell, 2027)

Multi-omics Mendelian randomization and machine learning identify candidate therapeutic targets for Alzheimer’s and Parkinson’s diseases - Xun Li; Lei Zhang; Jinyan Xia; Meiling Zheng; Zhipeng Zhou; Jing Cai (Mammalian Genome, 2026)

Exogenous dissolved organic matter redirects humic carbon fate at mineral interfaces through pre-contact molecular conditioning - Yu Li; Guangxu Mi; Jianghao Cheng; Meiling Zhang; Ying Liu; Shuang Ai; Fan Yang; Kui Cheng (Water Research, 2026)

Multiscale characterization and velocity-related risk zoning of impact damage in mature broccoli under controlled single-impact simulation - Liming Qin; Meiling Yuan; Zheng Xu; Jiajun Wu; Jingbin Li (Postharvest Biology and Technology, 2026)

Nonlinear buckling responses of a confined liner reinforced by functionally graded graphene with atom vacancy defects under thermal-mechanical loading - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Engineering Structures, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Integrated biochar-iron amendment mitigates rice cadmium uptake via soil immobilization, iron plaque barriers, and microbial community restructuring - Meiling Xu; Tianyi Hu; Fangge Xu; Jing Che; Guobing Wang; Yepu Li; Qiao Xu; Xiaozhi Wang (Journal of Environmental Chemical Engineering, 2026)

Comparative Lipidomics and microstructural characterization of Milk fat globule membrane protein powders from bovine buttermilk and cheese whey - Kuolin Si; Mengxueyao Zhang; Xuexing Zong; Yin Pei; Lu Liu; Xiuxiu Zhang; Meiling Ge; Xiaodong Li; Qingquan Yan (Food Research International, 2026)

Dietary compound probiotics enhance milk fat production, nutrient digestibility, and modulate hindgut health in lactating dairy cows - Danni Wei; Suran Liu; Meiling Zheng; Ming Deng; Baoli Sun; Yaokun Li; Guangbin Liu; Dewu Liu; Wenfeng Hu; Qingshen Liu; Yongqing Guo (Animal Feed Science and Technology, 2026)

Chemical reaction driven interfacial reconstruction of In2O3/S-BiOCl heterojunction with Ag2S quantum dots enables a self-validated fluorescence/photoelectrochemical dual mode nitrite sensing - Jingshu Li; Yuee Zhong; Manqi Li; Jiawei Zhou; Hengwen Tang; Jing Liu; Jianru Tang; Xiaohua Zhu; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2026)

A double-platform assay for rapid and on-site detection of chikungunya virus by integrating catalytic hairpin assembly with lateral flow immunochromatography assay - Ruijie Lu; Dawen Chen; Ai Chen; Shuo Ma; Yuming Yao; Yaya Chen; Gulinaizhaer Abudushalamu; Meiling Zhou; Xiao Li; Yue Zheng; Wenjing Lu; Yueqi Wang; et al. (Analytica Chimica Acta, 2026)

Remediation of Black and Odorous Water using a Slow-release Composite Agent Containing CaO2, Zeolite, and Polymeric Ferric Sulfate: Effects on Water Quality and Chlorella Growth - Jinhai Li; Defu Xu; Yafei Xun; Ying Zhuang; Meiling Guan; Alan Howard (Water, Air, & Soil Pollution, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Artificial humic acid reshapes microbial C-N metabolism and nitrogen partition in microplastic-contaminated soils - Qihe Gao; Shuang Ai; Meiling Zhang; Yu Li; Yantong Li; Yadong Ma; Jiale Zhang; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

Inner Ear Organoids: Recent Progress and Challenges - Yingxinyu Li; Cairong He; Jiayan Liu; Haiqin Zhang; Hongxia Zhang; Zheyu He; Mengyang He; Meiling Chen; Feiyan Zhou; Jie Ding (Stem Cell Reviews and Reports, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Synergistic T cell and microbiome dysregulation in FOXP3-mediated immune enteritis: insights from multimodal omics - Meiling Jin; Cheng Jin; Shunlai Shang; Yuqing Gu; Peng Jin; Haibin Yu; Diangeng Li (Science China Life Sciences, 2026)

Emapalumab plus conventional therapy with or without ruxolitinib for pediatric hemophagocytic lymphohistiocytosis: a single center retrospective study - Meiling Liao; Li Xiao; Min Gu; Jie Yu (Immunologic Research, 2026)

Pseudomonas aeruginosa in Chinese mitten crab Eriocheir sinensis: Identification, pathogenic potential and control with Bdellovibrio powder - Li He; Yueqi Yang; Yiyao Liu; Meiling Liu; Haipeng Cao; Chunlei Gai; Weidong Ye (Journal of Invertebrate Pathology, 2026)

Linking molecular heterogeneity of artificial humic acid to divergent cadmium coordination behaviors - Yu Li; Xianghui Meng; Shuang Ai; Meiling Zhang; Guangxu Mi; Yurun Miao; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Bionic construction and performance assessment of 3D bioprinted small-diameter artificial blood vessels - Yuan-Zhu Xin; Wenyu Jin; Qianqian Wu; JunHee Lee; Geng Li; Yan Chen; Jun Liu; Seok-Jo Yang; Jiazi Gao; Meiling Quan; Zhenning Liu (Chemical Engineering Journal, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Seamless 1-km hourly land surface temperature estimation via multi-source data integration and automated machine learning - Yumin Li; Meiling Gao; Zhenhong Li; Penghai Wu; Bin Wang; Rongtang Xu; Guijun Yang (Urban Climate, 2026)

Buckling of the constrained subsea FGP-GPLs liner under pressure loading and heating field based on multi-source data fusion scheme - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Ocean Engineering, 2026)

Dissolved organic matter dynamics and antibiotic resistance gene attenuation during composting: Characteristics and interrelationships - Dongfang Shi; Meiling Shi; Shengnan Zhang; Pengyan Zhang; Xiaoyan Qian; Yongjun You; Chong Liu; Fayong Li (Journal of Environmental Chemical Engineering, 2026)

Removal of organochlorine from the oil phase by poly(BMA-co-SMA-co-DAP) acrylic resin: Adsorption selectivity, kinetics, thermodynamics, molecular simulation and DFT calculations - Pan Luo; Xi Deng; Yingchun Lu; Meiling Li; Guihong Lan; Haiyan Qiu; Bo Xu; Yinli Peng (Journal of Environmental Chemical Engineering, 2026)

Study on the removal effect of Enteromorpha polysaccharide on heavy metal-organic composite pollution - Xue Shen; Yingqiang Li; Meiling Li; Yaru Zai; Xue Han; Shida Zhang; Jin Wang; Zhigang Yang; Yang Song (Journal of Environmental Chemical Engineering, 2026)

Facet and crystallinity-dependent transformation of lepidocrocite impacts cadmium redistribution - Meiling Yin; Jin Wang; Songxiong Zhong; Xiaofei Li; Fei Huang; Chen Yang; Fangbai Li; Zhi Dang; Chuling Guo (Environmental Pollution, 2026)

Elevated CO2 synergizes with nanoplastics to intensify arsenic mobilization, biotransformation, and plant uptake in soil-spinach systems - Wei Li; Yabo Wang; Yuling Suo; Zishu Zheng; Qiao Xu; Meiling Xu; Fen Xu; Weiqin Yin; Shengsen Wang; Xiaozhi Wang (Environmental Pollution, 2026)

Impacts of vegetation management on pollination network structure and robustness in urban parks: A case study from Beijing Wenyu River Park - Yaxuan Li; Meiling Shu; Chenxi Li; Liwen Liu; Yan Zhou; Lan Wu; Yuyu Wang (Urban Ecosystems, 2026)

Aneuploid gametes produced by triploid Populus ‘Beilinxiongzhu 1#’ transmit higher paternal heterozygosity to progeny - Yaru Sang; Yunyun Xie; Yifan Zhao; Bo Kong; Dawei Cheng; Liang Li; Lexun Ma; Jiahua Du; Meiling Long; Dongliang Cao; Zhang Huajian; Lao Huiqi; et al. (Tree Genetics & Genomes, 2026)

Preliminary study on targeted therapy of breast cancer using tumor cell membrane-coated dual-loaded liposomes based on chemo-photothermal synergistic effects - Yuwei Wang; Shuchao Pang; Yun Lu; Xialin Guo; Chanlian Li; Meiling Chen; Xiaoliang Ren (Drug Delivery and Translational Research, 2026)

Drug-Induced Noninfectious Myocarditis/Pericarditis: A Real-World Pharmacovigilance Study Using the FAERS Database - Shijie Zhao; Weiyi Chen; Chao Tao; Ke Wang; Liuxuan Yang; Ruixiao Li; Meiling Zhou; Jinlu Shang; Xianbin Liu (Cardiovascular Toxicology, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Characteristics of the microbial carbon pump in kelp farming areas and the impact of artificial reefs: A metagenomic and ecological perspective - Junyang Ma; Jihua Liu; Zhansheng Guo; Meiling Zhu; Zitong Chai; Feng Jiang; Zhu Li; Zhenlin Liang; Zhaoyang Jiang (Environmental Research, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Effects of different dark septate endophyte species on growth, Pb tolerance and associated physiological responses in Astragalus membranaceus under Pb stress - Gen Li; Meiling Wu; Qingqing Liu; Yashuo Tian; Simiao Wang; Yibang Zhang; Qing Dang; Fei Cao; Li Han (Plant and Soil, 2026)

Bidirectional gut-heart axis interactions in the context of predictive, preventive, and personalised medicine: a time-course analysis of comorbidity and mortality risk in a large population cohort - Meiling Cao; Di Liu; Haotian Wang; Cancan Li; Huapeng Lin; Lijuan Wu; Youxin Wang (EPMA Journal, 2026)

Association of metabolic status and genetic predisposition with healthy ageing and life expectancy across obesity levels: a prospective cohort study in the context of 3P medical approaches - Cancan Li; Haotian Wang; Huimin Lu; Meiling Cao; Jie Zhang; Shengzhi Sun; Youxin Wang (EPMA Journal, 2026)

Spatiotemporal Profiling of Intratumoral Free Payload Distribution via MALDI Imaging Mass Spectrometry: Implications for Drug-to-Antibody Ratio Optimization in Antibody–Drug Conjugates - Tingting Cai; Ziyi Li; Qiaofang Yan; Guangcun Huang; Kaiying Jia; Xiaotong Chen; Junling Dun; Jinghua Zou; Meiling Tan; Yue Wu; Fan Wang (The AAPS Journal, 2026)

Exogenous plant growth-promoting rhizobacteria boosting photosynthetic efficiency via thylakoid lipid restructuring in potato under low-potassium conditions - Xin Zhou; Xin Cheng; Baoyu Fu; Meiling Li; Chao Luo; Haoyang Gong; Hongkun Yang; Jingye Fu; Chengcheng Cai; Kaiqin Zhang; Shunlin Zheng (Plant Science, 2026)

Community characteristics and risks of disinfection residual bacteria (DRB) during intermittent chlorination of stored rainwater - Zhiwen Chen; Xiaobin Liao; Binxiong Hu; Ye Yang; Meiling Liu; Yingying Dong; Tao Li; Likun Lv; Mawuli Dzakpasu; Yuefeng Xie; Wendong Wang (Journal of Environmental Chemical Engineering, 2026)

Deep-sea bamboo corals: New Jasonisis species from Indian and Atlantic ridges and pan-oceanic genetic connectivity of Tridentisis candelabrum - Meiling Ge; Xinlong Li; Xin Tian; Ningxia Xu; Xuying Hu; Yu Xu; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

SREBP1-activated lipid metabolism drives ferroptosis and progression of clear cell renal cell carcinoma - Bao Wang; Junpeng Fu; Jian Qian; Yuang Wei; Meiling Bao; Haoqi Miao; Xinzhe Zhao; Kezheng Shao; Yuan Song; Ruoyun Tan; Jie Li; Pengfei Shao (Science China Life Sciences, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Impact of mid-high-latitude Eurasian ISO on extreme hot days in the middle-lower reaches of the Yangtze River valley during boreal summer - Meiling Zhang; Shuangyan Yang; Zhiwei Zhu; Tim Li (Climate Dynamics, 2026)

Coupled crack-rainfall mechanism of a retrogressive landslide: field investigation and monitoring in Southwest China - Qiuxiang Huang; Shupeng Li; Meiling Xiong; Chu Zhang; Yan Zhou (Bulletin of Engineering Geology and the Environment, 2026)

Spatiotemporal temperature variations induced by urban extreme heat events at the micro-scale - Huifang Li; Shuman Shen; Meiling Gao; Yu Wu; Zhihua Wang; Huanfeng Shen (Urban Climate, 2026)

Study on ball milling driven solvent extraction – Ozone oxidation decolorization of waste printed polyester fabrics - Xiao Li; Chengyong Gao; Wansi Li; Sheng Shi; Enbin Zhu; Meiling Zhang; Shuhua Wang (Process Safety and Environmental Protection, 2026)

Effects of humic acid and microbial agents on contaminated manure composting: Heavy metal passivation, gaseous emission mitigation and microbial community response - Meiling Shi; Xiaojuan Wang; Jie Gu; Xuefei Hu; Fayong Li; Yongjun You; Pengyan Zhang (Process Safety and Environmental Protection, 2026)

A mid-Cretaceous (late Albian–early Turonian) stable isotope record from southern Tibet – Pristine or diagenetically altered? - Meiling Han; Gang Li; Alexander Wheeler; Ulrich Heimhofer; Jörg Mutterlose (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A bacteriohopanetetrol stereoisomer in Western Pacific oxycline indicates anammox-driven nitrogen loss and warm eddy dynamics - Liqin Duan; Jinming Song; Meiling Yin; Xiaowei Wang; Chuanyu Liu; Jiawei Kan; Zhuoyue Wang; Feng Zhao; Xuegang Li; Huamao Yuan (Geochimica et Cosmochimica Acta, 2026)

Stability and Transport of Ferrihydrite Nanoparticles in Alkaline Soils - Yan Gong; Meiling Wang; Shuting Tian; Qingwei Ding; Xia Li; Gaiqiang Yang; Qi Liu; Juanfang Yang; Lijuan Huo (Water, Air, & Soil Pollution, 2026)

Research on high-resolution PM2.5 concentration estimation methods based on transfer learning - Meiling Xing; Bo Li; Wenhao Zhang; Guohong Li; Xiufeng Yang; Qiyue Liu; Qichao Zhao (Advances in Space Research, 2026)

Ecological distribution and functional characterization of polyethylene-degrading enzymes from diverse metagenomes - Ning Wang; Meiling Jin; Zixuan Zhu; Yuxin Wang; Xinyu Li; Jing Xu; Shijunyi Cheng; Yuanying Zhu; Ruiqi Wang; Tong Xu; Furong Yin; Xinyue Li; et al. (Science of The Total Environment, 2026)

The changes of antioxidant system, membrane integrity and phenolics metabolism participate in bongkrekic acid and adenosine triphosphate-mediated energy status regulating longan pericarp browning - Meiling Li; Hetong Lin; Ruiling Zhuo; Boqiang Li; Yifen Lin; Yihui Chen; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2026)

Porous Eu-ox metal–organic framework enabling open-channel carrier transport and durable Pb2+ immobilization in perovskite solar cells - Zhihang Zhang; Xiaolong Cao; Tiantian Lv; Zhengyan He; Haiyan Sun; Hai Zhong; Qi Zhang; Changlin Yao; Wen Li; Shufang Zhang; Meiling Feng (Chemical Engineering Journal, 2026)

Predicting ecological risks of heavy metals in watersheds based on interpretable machine learning models: under the framework of data scarcity - Hong Chen; Meiling Kong; Zhenghua Wu; Liu Gong; Lanlan Huang; Yihan Li; Fazhi Xie (Environmental Monitoring and Assessment, 2026)

Underwater Noise in Offshore Wind Farms: Monitoring Technologies, Acoustic Characteristics, and Long-Term Adaptive Management - Peibin Zhu; Zhenquan Hu; Haoting Li; Meiling Dai; Jiali Chen; Zhuanqiong Hu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The rapid global expansion of offshore wind energy (OWE) has established it as a critical component of the renewable energy transition; however, this development concurrently introduces significant underwater noise pollution into marine ecosystems. This paper provides a comprehensive review of the acoustic footprint of OWE across its entire lifecycle, rigorously distinguishing between the high-intensity, acute impulsive noise generated during pile-driving construction and the chronic, low-frequency continuous noise associated with decades-long turbine operation. We critically evaluate the engineering capabilities and limitations of current underwater acoustic monitoring architectures, including buoy-based real-time monitoring nodes, cabled high-bandwidth systems (e.g., cabled hydrophone arrays with DAQ/DSP and fiber-optic distributed acoustic sensing, DAS), and autonomous seabed archival recorders (PAM deployment). Furthermore, documented biological impacts are synthesized across diverse taxa, ranging from auditory masking and threshold shifts in marine mammals to the often-overlooked sensitivity of invertebrates and fish to particle motion—a key metric frequently missing from standard pressure-based assessments. Our analysis identifies a fundamental gap in current governance paradigms, which disproportionately prioritize the mitigation of short-term acute impacts while neglecting the cumulative ecological risks of long-term operational noise. This review synthesizes recent evidence on chronic operational noise and outlines a conceptual pathway from event-based compliance monitoring toward long-term, adaptive soundscape management. We propose the implementation of integrated, adaptive acoustic monitoring networks capable of quantifying cumulative noise exposure and informing real-time mitigation strategies. Such a paradigm shift is essential for optimizing mitigation technologies and ensuring the sustainable coexistence of marine renewable energy development and marine biodiversity.

Evaluation of the antibacterial and antioxidant potential of the endophytic fungus EFY14 from Cannabis sativa L. leaves through metabolomics and molecular docking - ShanShan Li; MeiLing Zhang; Ying Zhai; Yan Zhao; Ming Zhao; LiJie Liu; FeiYao Zhong; ZhiGang Wang; Shuai Li (Natural Product Research, 2026)

Seasonal gut microbiota and functional dynamics in brittle star (Ophiothrix exigua) from the Yellow Sea, China - Md. Tariful Islam Fuad; Yue Dong; Zhong Li; Meiling Ge; S.M. Sharifuzzaman; Xiaoshou Liu; Xuelei Zhang; Qinzeng Xu (Marine Environmental Research, 2026)

Disentangling adaptive strategies of eukaryotic phytoplankton to environmental stressors in the sediment-laden Yellow River: A multi-method perspective from eDNA and morphology - Meiling Yi; Shuang Xu; Feilong Li; Bowen Gao; Yang Li (Environmental Research, 2026)

Genetic context-dependent regulation of FlbE enhances morphology modulation and citric acid production in Aspergillus niger - Meiling Chen; Xiaomei Zheng; Peng Du; Xiaomeng Ni; Zhimin Li; Ping Zheng; Jibin Sun (Bioresource Technology, 2026)

Tetrahydrocurcumin for Major Depressive Disorder with Therapeutic Potential and Mechanistic Insights from Clinical and Preclinical Studies - Ying Guo; Jianping Xie; Haiyun Luo; Yun Yuan; Fang Long; Jingyuan Meng; Hui Tan; Yuanping Li; Bibo Cai; Meiling Chen; Liyan Yang; Jingmei Zhong; et al. (Molecular Neurobiology, 2026)

Reciprocal rate-modulated evolution of slow-moving reservoir landslide: learning from hydrological-adapted block model - Shu Zhang; Qiang Li; Huiming Tang; Zongxing Zou; Jianfan Zhao; Jiefei Zhang; Meiling Wu (Landslides, 2026)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

Monsoonal intensity dominated the Eocene evolution of paleovegetation and paleoclimate in northern South China Sea - Jinhua Zeng; Tao Jiang; Keqiang Wu; Desheng Hu; Yong Man; Licheng Cao; Cong Cheng; Zigui Chen; Kun Wang; Nan Bai; Meiling Feng; Ziyi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effects of long-term plastic film mulching on microplastic and phthalate esters pollution in salt-affected soils: Microbial community shifts and enrichment of putative degraders - Jiabin Li; Yunfeng Pu; Yongjun You; Shengnan Zhang; Xiaoyan Qian; Meiling Shi; Guocai Ma; Chong Liu; Kamel M. Eltohamy; Fayong Li (Journal of Hazardous Materials, 2025)

Application of soda residue based material in a vertical flow constructed wetland for the simultaneous removal of tetracycline and phosphorus from freshwater aquaculture effluent - Ye Yang; Binxiong Hu; Tao Li; Meiling Liu; Ahmed Omer Abdalrahim Mohamed; Yingying Dong; Mawuli Dzakpasu; Hang Li; Yingyue Wang; Wendong Wang (Journal of Environmental Chemical Engineering, 2025)

Manufacture of a fluorescent covalent organic framework and its Eu3 + -functionalized material for the design of dual-functional platforms for fluorescent and colorimetric sensing - Yuqiang Xiao; Jiaqi Hu; Mingyue Wang; Yue Lan; Dandan Wang; Famin Ke; Lingling Li; Minmin Wang; Leijiao Peng; Meiling Yang; Tianzhen Gao; Jianming Wu; et al. (Journal of Environmental Chemical Engineering, 2025)

Structure design and future development of lithium ion sieve bulk adsorbents - Rongye Zhang; Chenyang Li; Meiling Wang (Journal of Environmental Chemical Engineering, 2025)

Changes in soil quality and crop productivity along rice cultivation chronosequences in saline-alkali soils - Bangyan Zhang; Jinmin Wu; Xiaolong Bai; Lei Li; Meiling Lin; Xing Xu; Fengju Zhang; Bin Wang (Journal of Environmental Management, 2025)

Laser-engineered rattan evaporators for scalable and sustainable solar desalination - Haocheng Xu; Yingpeng Liu; Pei Qi Woon; Meiling Chen; Xinwu Xu; Bofan Li (Chemical Engineering Journal, 2025)

Multi-mechanism collaborative photocatalytic CH4 conversion over Cu/ZnS/ZnOx-550 Z-scheme heterojunction - Weixin Li; Qing Liu; Zhongxuan Yin; Yongqing Ma; Ganhong Zheng; Chuhong Zhu; Zhenxiang Dai; Meiling Wang (Chemical Engineering Journal, 2025)

The BBX Gene Family in Papaya (Carica papaya L.): Genome-Wide Identification and Expression Profiling During Fruit Ripening - Meiling Ding; Shengjie Li; Jialin Hu; Sicheng Bai; Xianqi Fu; Zhimiao Liang; Xiaomin Liang; Yating Li; Miaoyu Zhao (Tropical Plant Biology, 2025)

PPAR γ changing ALDH1A3 content to regulate lipid metabolism and inhibit lung cancer cell growth - Xinyuan Tian; Xiaoping Bai; Yunqi Han; Yu Ye; Meiling Peng; Hongwei Cui; Kai Li (Molecular Genetics and Genomics, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

AKR1B1 is Required for Maintaining Acute Leukemia Cell Survival by Epigenetic Silencing of Tumor Suppressor Genes - Jingyu Chen; Lu Xu; Wangshi Li; Meiling Sun; Yao Chen; Ting Qiu; Yue Wu; Xingzhi Lv; Fukai Liu; Huitao Fan (Biochemical Genetics, 2025)

A novel “WRF+AutoML” framework for enhanced heat estimation in urban environments - Meiling Gao; Huifang Li; Fei Chen; Mengzi Zhou; Guijun Yang; Dun Zhu; Dawei Han; Zhenhong Li (Sustainable Cities and Society, 2025)

One stone, several birds: A carboxyl-carbazole-rich fluorescent covalent organic framework for the detection of tetrabromobisphenol S, Fe³ ⁺, ascorbic acid, D/L-arginine, and the removal of tetrabromobisphenol S - Jiaqi Hu; Mingyue Wang; Min Wang; Dandan Wang; Yuqiang Xiao; Yue Lan; Lingling Li; Meiling Yang; Minmin Wang; Leijiao Peng; Famin Ke; Xiurong Guo; et al. (Journal of Hazardous Materials, 2025)

Drainage reorganization near the eastern margin of the Tibetan Plateau as a result of fluvial response to differential uplift enhanced by isostatic compensation - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Zijuan Dong; Xiaohua Li; Meiling Zhong; Renzhe Pan; Ningyi Li; Rob Westaway (Global and Planetary Change, 2025)

Possible influences of tropical vegetation shift on the glacial-interglacial temperature changes - Liping Tian; Cong Chen; Mengyuan Wang; Chuanxiu Luo; Xiao Zhang; Yanming Ruan; Jiantao Cao; Meiling Man; Zhuo Zheng; Xiaoqiang Yang; Kangyou Huang; Li Li; et al. (Global and Planetary Change, 2025)

Alternating current charging-strengthened anode interface and cathode prelithiation synergistically improve comprehensive performances of LiFePO4||graphite batteries - Meiling Wu; Yulong Zhang; Shiyou Li; Lei Niu; Ningshuang Zhang; Xiaoling Cui (Chemical Engineering Journal, 2025)

Fast prediction of indoor temperature distribution under spatiotemporal variation of solar radiation using equivalent surface heat sources and multimodal CNN - Ye Yuan; Junxi Gao; Meiling Li; Gang Liu; Yuebo Yu; Zixuan Yu; Hanyuan Zhang (Building and Environment, 2025)

Sequential temperature design in high-speed railway stations: A dynamic thermal strategy balancing thermal comfort and energy efficiency - Ye Yuan; Meiling Li; Junxi Gao; Gang Liu; Zongwu Xu; Ying Chen; Hanyuan Zhang (Building and Environment, 2025)

Impacts of turbulent intermittency and pressure oscillation on persistent heavy haze pollution - Qianhui Li; Wei Wei; Hongsheng Zhang; Meiling Sun; Bingui Wu; Jingle Liu (Atmospheric Research, 2025)

Construction of fibromodulin and borneol-clacked phosphorus dendrimer nanoparticles to reduce inflammation and oxidative stress in BBB to nursing care and ischemic stroke therapy - Tian Li; Xin Jia; Meiling Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Wheat yield prediction using an enhanced WOFOST with soil stratified hydrothermal module driven by GLASS and ERA5-land products over Yellow River Basin - Jing Zhang; Guijun Yang; Meiling Gao; Lijie Zhang; Weinan Chen; Miao Liu; Youming Zhang; Aohua Tang; Zhenhong Li (Computers and Electronics in Agriculture, 2025)

Computed method for the thermal buckling performance of a constrained non-circular heated pipeline with an oval inverted arch - Qian Zhang; Shiyi Zhang; Meiling Shen; Zhaochao Li (Tunnelling and Underground Space Technology, 2025)

DNP and ATP regulate disease progression in Neopestalotiopsis clavispora-infected guava fruit by modulating respiratory and energy metabolism - Hongbin Chen; Yifei Chen; Xuanjing Jiang; Yuzhao Lin; Yazhen Chen; Meiling Li; Yihui Chen (Postharvest Biology and Technology, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Hierarchically superhydrophobic ceramic fiber membrane with thermal-induced pore modulation for antifouling oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Huaiyuan Wang (Chemical Engineering Journal, 2025)

The intergrowth of YTa7O19 in L-Ta2O5 with Er3+/Yb3+ enhancing pure green upconversion luminescence intensity by molten salt synthesis - Yuhan Fan; Yongze Cao; Zhihua Zhang; Hualong Tao; Meiling Li; Xizhen Zhang; Sai Xu; Baojiu Chen (Chemical Engineering Journal, 2025)

CO2 adsorption and separation properties of decorative paper impregnated with amino-functionalized cellulose nanofibers/waterborne acrylic resin - Xiaopin Bu; Qian Wei; Zhuoxin Liao; Yuding Zhu; Meiling Chen; Junhui Yang; Xiuzhen Lin; Donggyun Kim; Xiangyu Wang; Song Li; Jeonghun Kim; Wenkai Zhu (Chemical Engineering Journal, 2025)

CBT-Cys click ligation coupled with pregnancy test strips for nucleic acid assay - Meiling Zhang; Jiahang Song; Huawen Zhang; Yang Li; Xu Hun (Analytica Chimica Acta, 2025)

Bacteriochlorophyll reveals estuarine hypoxia and anoxygenic photosynthetic carbon fixation - Jiawei Kan; Liqin Duan; Jinming Song; Meiling Yin; Xuegang Li; Xiaoqi Liu; Huamao Yuan; Yingxia Wang (Limnology and Oceanography, 2025)
Bacteriochlorophylls (Bchls) are photosynthetic pigments produced by aerobic anoxygenic photosynthetic bacteria and anoxygenic photosynthetic bacteria. However, the sources, degradation, and influence of redox conditions in marine environments remain unclear. This study investigated the distribution of Bchls in the Changjiang Estuary to evaluate their origins, degradation, and environmental response. Results showed that total bacteriochlorophylls a (T Bchl a ), including bacteriochlorophyll a (Bchl a ) and its degradation product bacteriopheophytin a (Bphe a ), were higher in surface waters than in bottom waters in the inner estuary, where microbial evidence ( Sphingomonadaceae ) identified aerobic anoxygenic photosynthetic bacteria as the dominant source of T Bchl a . In contrast, the outer estuary exhibited elevated T Bchl a in bottom waters, with purple sulfur bacteria ( Chromatiaceae and Ectothiorhodospiraceae ) as the primary contributors. Significant negative correlations between Bphe a concentrations in bottom seawaters and surface sediments and the dissolved oxygen levels in bottom waters, along with a positive correlation between Bphe a in the surface sediments and the salinity difference between bottom and surface seawaters (Δ S ), suggest that Bphe a may serve as a useful indicator of hypoxia and water stratification. The contribution of anoxygenic photosynthetic bacteria to carbon fixation is expected to increase notably, potentially reaching 16% of phytoplankton carbon fixation after 100 years under expanding hypoxia. These findings establish Bchls as reliable indicators of hypoxia and water stratification and provide a framework for reevaluating carbon fixation in global hypoxic coastal systems.

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Impacts of human activities on vegetation dynamics amid climate change: A case study of the Hanjiang River Basin (China) - Xiaofei Li; Peiyue Li; Meiling Gao; Dawei Mu; Dawei Han (Journal of Environmental Management, 2025)

Robust cyclic olefin thermoplastic elastomer with excellent mechanical and thermal performance - Xiaohui Mao; Meiling Pu; Yuanbo Liu; Zhe Ma; Li Pan; Yuesheng Li (Chemical Engineering Journal, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

The high economic cost of biological invasions in China - Yuanyi Li; Jinyu Zhang; Jun Zhang; Jiacong Du; Ruxiang Yang; Meiling Niu; Yiming Li (Journal of Environmental Management, 2025)

Respective contribution of varied reactive oxygen species formed in methane conversion over calcined ferric sulfate - Qing Liu; Weixin Li; Zhongxuan Yin; Yongqing Ma; Ganhong Zheng; Chuhong Zhu; Meiling Wang (Journal of Environmental Chemical Engineering, 2025)

Reorganization of antecedent rivers in response to the evolving landscape at the northeastern margin of the Tibetan Plateau - Baotian Pan; Zijuan Dong; Zhenbo Hu; David Bridgland; Qinhong Mo; Xiaohua Li; Menghao Li; Yanan Yang; Meiling Zhong; Renzhe Pan (Earth-Science Reviews, 2025)

Impact of environmental salinity on the MAPK-NFAT5 pathway in Trachemys scripta elegans and its role in osmoregulaton - Xin Niu; Yingnan Lu; Yue Yuan; Jiao Li; Yunjuan Xiao; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Environment disturbances influence bacterial diversity, structure and co-occurrence network in the Digitaria sanguinalis rhizosphere - Yiming Dai; Ye Cui; Qingchen Xiao; Meiling Ping; Yiming Zhang; Shiguang Hu; Hao Chen; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2025)

Calcium isotope composition of the Gangdese continental arc deep crust and implications for making continental crust - Meiling Wang; Zaicong Wang; Liang Guo; Zongqi Zou; Fei Wu; Wei Dai; Jingliang Guo; Kang Chen; Lanping Feng; Haihong Chen; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2025)

CO2 selective adsorption from CO2/CH4 mixtures and regeneration of X zeolites by Li and K modification using various regeneration strategies - Yongbiao Sun; Hui Li; Haijun Lai; Yan Yu; Meiling Hou; Chao Fu; Zaizhou Wang; Chunxiang Zhang (Chemical Engineering Journal, 2025)

Hypoxia-activated and status-reversing hydrogel platform initiates potent systemic immunity against triple-negative breast cancer - Zhike Li; Xianzhou Huang; Jin Yang; Meiling Shen; Yanjie You; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2025)

GDF11 Regulates M1 and M2 Polarization of BV2 Microglial Cells via p38 MAPK Signaling Pathway - Xiangyu Zhao; Rui Qin; Guopeng Li; Gaorong Lv; Di Zhao; Linghua Kong; Meiling Qi; Ping Li (Molecular Neurobiology, 2025)

Late Albian–early Turonian calcareous nannofossils from southern Tibet — Implications for preservation, biostratigraphy and palaeoecology - Meiling Han; Gang Li; Ulrich Heimhofer; Jörg Mutterlose (Cretaceous Research, 2025)

Characteristics and mechanisms of sea (salt) water intrusion in Laizhou City, Shandong Province, China - Linghao Kong; Hongxian Chu; Guohua Hou; Jiao Zeng; Liyuan Zhao; Xiangcai Han; Yachao Li; Faqiao Zhou; Meiling Yin; Xuzhen Zhang (Frontiers in Marine Science, 2025)
Sea (salt) water intrusion is a significant and ongoing geological disaster, and in recent years, it has become a notable concern for Laizhou City, Shandong Province. To identify the characteristics and mechanism of sea (salt) water intrusion in Laizhou City, samples of different types of water bodies (such as seawater, freshwater, slightly brackish water, brackish water, saline water, and brine) were systematically collected from the coastal zone area. The hydrochemical composition and evolution characteristics of the water bodies and the current situation, trends, and causes of sea (salt) water intrusion were analyzed. In 2020, the sea (salt) water intrusion reached 645.76 km 2 (including 151.64 km 2 of serious intrusion area), which is the largest ever recorded. The sea (salt) water intrusion had a strip-sheet distribution. From land to sea, groundwater gradually transitioned from the HCO 3 ·SO 4 ·Cl-Ca type to SO 4 ·Cl-Na·Ca and SO 4 ·Cl-Na types and then evolved to the Cl-Na type. Furthermore, from land to sea, the dominant cations and anions shifted from Ca 2+ and HCO 3 - to Na + and Cl - . The influence of seawater or brine gradually increased, that of Ca 2+ and HCO 3 - gradually decreased; whereas that of Cl - and Na + gradually increased, showing a division zone of freshwater → slightly brackish water → brackish water → saline water → seawater (brine) in the macroscopic territory. The freshwater, slightly brackish water, and brackish water bodies in the study area were controlled by evaporation and concentration processes and rock weathering leaching, whereas the saline water and brine were primarily controlled by evaporation and concentration processes. Groundwater salinity in the study area mainly originates from sea (salt) water intrusion, and locally groundwater salinity mainly originates from mineral dissolution or human activities. In addition, significant cation exchange adsorption occurred in slightly brackish and brackish water. Overall, these results will help to prevent and control seawater intrusions and improve disaster management.

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Characteristics and mechanism of paclobutrazol degradation by the novel bacterial strain Kurthia gibsonii CGMCC 32305 - Wenxin Zhang; Meiling Shi; Yue Lou; Xinyi Liu; Xiaoli Dai; Yang Liu; Zhaoyu Li; Xu Su; Jiajia Li; YongQiang Tian (Journal of Environmental Chemical Engineering, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Microbial mechanism and CO2 emission from coastal saline soil: The role of corn stover and nutrient additions - Qiao Xu; Ling Zhang; Yingdong Zhao; Caixian Tang; Yinjuan Li; Meiling Xu; Xiaozhi Wang (Environmental Research, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Recycling of waste denim: A stepwise utilisation strategy for clean decolourisation, opening and degradation - Zhao Li; Meiling Zhang; Fei Li; Sheng Shi; Shuhua Wang; Chengyong Gao; Yiming Li (Waste Management, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

RealFusion: A reliable deep learning-based spatiotemporal fusion framework for generating seamless fine-resolution imagery - Dizhou Guo; Zhenhong Li; Xu Gao; Meiling Gao; Chen Yu; Chenglong Zhang; Wenzhong Shi (Remote Sensing of Environment, 2025)

Divergent trends in vegetation greenness and resilience across China's forestry ecological engineering regions - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Ecological Engineering, 2025)

Enhanced hydrogen storage performance of Mg(BH4)2 with in-situ generated TiO2 and TiH2 catalysts - Zhenxuan Ma; Jiaguang Zheng; Ao Xia; Qingbo Zhang; Meiling Lv; Cong Li; Panpan Zhou (Chemical Engineering Journal, 2025)

The design of novel lithium salt additives: 4-benzonitrile-1,3-double (trimethylboric acid) lithium (LBTA) to endow inherent superior stability in high voltage lithium ion batteries - Lucheng Li; Meiling Liu; Peng Yang; Wenfeng Yuan; Jun Chen (Chemical Engineering Journal, 2025)

Evolution of vegetation phenology and its response to urbanisation in Shaanxi province, China: A fine-scale perspective - Meiling Gao; Jingjing Ma; Zhenhong Li; Guijun Yang (Journal of Geographical Sciences, 2025)

Ecosystem resilience response to forest fragmentation in China: Thresholds identification - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Journal of Environmental Management, 2025)

Multi-residue analytical method development and dietary exposure risk assessment of 345 pesticides in mango by LC-Q-TOF/MS - Xingqiang Wu; Jianxun Li; Jing Wei; Kaixuan Tong; Yujie Xie; Qiaoying Chang; Xiaoxuan Yu; Bei Li; Meiling Lu; Chunlin Fan; Hui Chen (Food Control, 2025)

Spatiotemporal changes of vegetation in the northern foothills of Qinling Mountains based on kNDVI considering climate time-lag effects and human activities - Lili Chen; Zhenhong Li; Chenglong Zhang; Xinxin Fu; Jiahao Ma; Meiling Zhou; Jianbing Peng (Environmental Research, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Correction to: Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Deuterium in drinking water and its effects on cancer and longevity - Meiling Zhong; Jiaxue Wang; Ouyi Zhao; Qiuyi Li (Isotopes in Environmental and Health Studies, 2025)

Unraveling the effects of extreme heat conditions on urban heat environment: Insights from local climate zones and integrated temperature data - Bin Wang; Meiling Gao; Yumin Li; Zhenhong Li; Zhenjiang Liu; Xuesong Zhang; Ying Wen (Sustainable Cities and Society, 2025)

Impact of humidity variations at different distances from the lake surface on rhizosphere microbiota of Trifolium repens L - Jin Chen; Meiling Ping; Xiaowan Geng; Keqing Lin; Boyan Wang; Yuxin Zhai; Yizhen Meng; Xiaoyu Li (Physiological and Molecular Plant Pathology, 2025)

Estimation of winter wheat yield by assimilating MODIS LAI and VIC optimized soil moisture into the WOFOST model - Jing Zhang; Guijun Yang; Junhua Kang; Dongli Wu; Zhenhong Li; Weinan Chen; Meiling Gao; Yue Yang; Aohua Tang; Yang Meng; Zhihui Wang (European Journal of Agronomy, 2025)

Autophagy in skeletal muscle dysfunction of chronic obstructive pulmonary disease: implications, mechanisms, and perspectives - Xiaoyu Han; Peijun Li; Meiling Jiang; Yuanyuan Cao; Yingqi Wang; Linhong Jiang; Xiaodan Liu; Weibing Wu (Journal of Zhejiang University-SCIENCE B, 2025)

Saikosaponins alleviate depression-like behaviors of chronic unpredictable mild stress exposed mice through ERK signaling pathway - Min Chen; Min Li; Liwei Ma; Huiling Hou; Meiling Tang; Qiang Li (Experimental Brain Research, 2025)

Liver transcriptome analysis reveals the molecular response to hibernation challenge in the Chinese soft-shelled turtle (Pelodiscus sinensis) - Muhammad Shahid Iqbal; Xiaoqi Ai; Qingjun Zhu; Ijaz Khan; Zeeshan Ali; Tian Lan; Li Ding; Meiling Hong (Frontiers in Marine Science, 2025)
Hibernation is a physiological strategy animals use to survive in hostile environments with extreme temperature challenges and food scarcity. During this state, significant changes occur in metabolism and cellular function, with numerous stress response pathways recalibrated to survive physiological challenges that could otherwise be fatal. Numerous studies were performed to explain the molecular mechanisms of mammalian hibernation, but detailed analyses remain scarce in reptiles. Given the limited understanding of the mechanisms regulating hibernation, we performed a comprehensive analysis of liver gene expression in the Chinese softshell turtle ( Pelodiscus sinensis ) comparing summer active (SA), hibernation (H), and early arousal (EA) states using RNA-sequencing. A total of 435 million high-quality reads were generated, identifying 3,508, 3,607, and 2,993 differentially expressed genes (DEGs) in the SA vs. H, H vs. EA, and EA vs. SA respectively. Gene ontology analysis revealed a shift in metabolic fuel utilization, with the down-regulation of metabolic and cellular processes during hibernation, reflecting a conserved strategy for energy conservation. The transition from hibernation to early arousal was marked by up-regulation of immune-related genes (e.g., CXCL12, ITGA4, PIGR) and endocrine regulators (e.g., CDKN1A, DLL4, IGF1R), facilitating metabolic recovery and cellular protection. Besides, we observed dynamic changes in carbohydrate and lipid metabolism, with down-regulation of hexokinase 2 (HK2) and glucose transporters during hibernation, and up-regulation of lipid metabolism genes (LSS, GPLD1) to support membrane integrity and signaling. Our findings provide insights into the molecular mechanisms underlying hibernation and arousal in ectotherms, with implications for understanding metabolic adaptations, immune regulation, and stress responses in extreme conditions.

Keystone taxa drive the synchronous production of methane and refractory dissolved organic matter in inland waters - Xinjie Shi; Wanzhu Li; Baoli Wang; Na Liu; Xia Liang; Meiling Yang; Cong-Qiang Liu (Water Research, 2025)

Melatonin treatment maintains the quality properties and storability of carambola fruit by modulating energy metabolism - Ting Hu; Shaojie Zheng; Qingqing Liu; Meiling Li; Jingyuan Chen; Huili Zhang; Mengshi Lin; Hetong Lin; Yihui Chen (Food Chemistry, 2025)

Abnormal sensory processing cortex in insomnia disorder: a degree centrality study - Hui Wang; Haining Li; Ziyi Liu; Chiyin Li; Zhaoyao Luo; Wei Chen; Meiling Shang; Huiping Liu; Fatemeh Naderi Nejad; Yuanping Zhou; Ming Zhang; Yingxiang Sun (Brain Imaging and Behavior, 2025)

Hypoxia exacerbate the marine ecological risk of arsenic: By stimulating its migration and release at the sediment-water interface - Liqin Duan; Jinming Song; Meiling Yin; Xiaoqi Liu; Xue Liu; Xuegang Li; Huamao Yuan (Water Research, 2025)

Effects of coexisting goethite or lepidocrocite on Fe(II)-induced ferrihydrite transformation pathways and Cd speciation - Meiling Yin; Xin Li; Chuling Guo; Qiaohui Zhong; Xiaofei Li; Lijuan Zeng; Yuting Zhou; Chen Yang; Zhi Dang (Science of The Total Environment, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

Structural modifications of berberine and the lipid-regulating effects of its derivatives - Yun Lu; Mengxuan Yin; Yuting Lai; Xinyi Ye; Meiling Chen; Yubo Li (Medicinal Chemistry Research, 2025)

Combined Effects of Cadmium and Lead on Growth Performance and Kidney Function in Broiler Chicken - Man Zhao; Longqiang Xie; Wenbin Huang; Meiling Li; Xin Gu; Wei Zhang; Jintao Wei; Niya Zhang (Biological Trace Element Research, 2025)

Dual-mode detection of human immunoglobulin via copper oxide nanozyme catalysis fluorescent species generation and photoelectrochemical alteration in ZnIn2S4/SnO2-based system - Jiawei Zhou; Lili Zhao; Yuee Zhong; Peipei Li; Xiaohua Zhu; Shu Huang; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2025)

Evaluation of the gully erosion susceptibility by using UAV and hybrid models based on machine learning - Qian Wang; Bohui Tang; Kailin Wang; Jiannan Shi; Meiling Li (Soil and Tillage Research, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Preparation of hydrophilic pulp cellulose-based membrane and its performance in oil-water separation - Qing Liu; Guorui Li; Kehui Qi; Huihui Zhang; Meiling Pu; Lu Li; Yanju Lu (Journal of Water Process Engineering, 2024)

Visible-light-assisted peroxymonosulfate activation using MIL-88A(Fe)/BiOI heterojunction composite to drive charge transport for eliminating acid red 18 - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hongna Zhang; Nannan Zhong; Hai-Ying Jiang (Journal of Environmental Chemical Engineering, 2024)

Similarity recognition approach to identify zero-added MSG soy sauce using stable isotopes and amino acid profiles - Chunlin Li; Meiling Sheng; Menglin Zhang; Karyne M. Rogers; Jing Nie; Shengzhi Shao; Jianbo Xiao; Yuwei Yuan (Food Chemistry, 2024)

Functionalization of cellulose by facile Dissolution-Regeneration in A novel CS2/DBU/DMSO solvent system for detection of metal ions and antibacterial - Yuyan Zheng; Zinan Li; Meiling Chen; Jiyang Zuo; Tao Yang; Wenhua Miao; Yadong Zhao; Fei Liu; Jinggang Wang; Jin Zhu (Chemical Engineering Journal, 2024)

MicroRNA expression profiles in plasma exosomes of late pregnant giant pandas - Meiling Cheng; Yingmin Zhou; Qian Wang; Bo Luo; Yanwu Lai; Jianbin Cheng; Xiuyue Zhang; Yan Huang; Desheng Li (Molecular Biology Reports, 2024)

Genome Mining Analysis Uncovers the Previously Unknown Biosynthetic Capacity for Secondary Metabolites in Verrucomicrobia - Xue Di; Peng Li; Jingxuan Wang; Vincent Nowak; Shuai Zhi; Meiling Jin; Liwei Liu; Shan He (Marine Biotechnology, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

Tectonic deformation and kinematics of fluvial terraces marking the northeastern margin of the Tibetan Plateau - Zijuan Dong; Baotian Pan; Zhenbo Hu; David Bridgland; Jun Wang; Rob Westaway; Menghao Li; Qinhong Mo; Xiaohua Li; Xilin Cao; Meiling Zhong; Renzhe Pan (Quaternary Science Reviews, 2024)

Analytical and numerical study on the dynamic responses of the buried offshore oval lined-pipeline system under strike-slip fault - Zhaochao Li; Shiyi Zhang; Meiling Shen; Hao Huang (Ocean Engineering, 2024)

Microbial inoculants using spent mushroom substrates as carriers improve soil multifunctionality and plant growth by changing soil microbial community structure - Hui Nie; Chong Li; Zhaohui Jia; Xuefei Cheng; Xin Liu; Qianqian Liu; Meiling Chen; Yong Ding; Jinchi Zhang (Journal of Environmental Management, 2024)

Thermal upheaval buckling framework of a graphene-reinforced subsea pipeline laid on an arched concave seabed - Zhaochao Li; Di Hu; Meiling Shen; Hao Huang; Zhihua Ou (Engineering Structures, 2024)

Monthly Precipitation Prediction Based on the CEEMDAN-BMA Model - Youyi Zhao; Shangxue Luo; Jiafang Cai; Zhao Li; Meiling Zhang (Water Resources Management, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

Interfacial charge demulsification endowed dual-network photocatalytic hydrogen-bonded PVA@agarose membranes for oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Liyan Liu; Huaiyuan Wang (Journal of Hazardous Materials, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Microbial regulation on refractory dissolved organic matter in inland waters - Wanzhu Li; Baoli Wang; Na Liu; Xinjie Shi; Meiling Yang; Cong-Qiang Liu (Water Research, 2024)

Synergistic enhancement of cadmium immobilization and soil fertility through biochar and artificial humic acid-assisted microbial-induced calcium carbonate precipitation - Yu Li; Meiling Zhang; Xiaobin Wang; Shuang Ai; Xianghui Meng; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2024)

Enhanced oxygen anions generation on Bi2S3/Sb2S3 heterostructure by visible light for trace H2S detection at room temperature - Meiling Yu; Jiayu Li; Dongmin Yin; Zhenze Zhou; Chenda Wei; You Wang; Juanyuan Hao (Journal of Hazardous Materials, 2024)

Designing a multi-level reverse logistics network for waste batteries of electric vehicles under uncertainty—A case study in the Yangtze River Delta Urban Agglomerations of China - Meiling He; Qipeng Li; Xiaohui Wu; Kazuhiro Izui (Journal of Cleaner Production, 2024)

The coupling between tectonic uplift and climate change recorded by the Yellow River terraces during the Zoige basin excavation in the northeastern Tibetan Plateau - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Ningyi Li; Zijuan Dong; Xiaohua Li; Yanan Yang; Meiling Zhong; Renzhe Pan; Rob Westaway (Geomorphology, 2024)

Progress in electrolyte regulation to enhance nitrogen reduction reaction - Qin Li; Xuguang Liu; Meiling Wang (Chemical Engineering Journal, 2024)

Nanoarchitectonics of bamboo-based heterojunction photocatalyst for effective removal of organic pollutants - Xiaole Yan; Meiling Chen; Junning Wang; Zhaodong Wang; Ruiqi Xin; Dujuan Wu; Ye Song; Song Li; Wenkai Zhu; Chaohai Wang; Yanli Mao (Chemical Engineering Journal, 2024)

2,3-pyridinedicarboxylic acid-modified MIL-88A(Fe) for enhanced peroxymonosulfate activation to degrade organic contaminants - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hai-Ying Jiang (Journal of Water Process Engineering, 2024)

Spatiotemporal variations of plankton communities in different water bodies of the Yellow River: Structural characteristics, biogeographic patterns, environmental responses, and community assembly - Meiling Yi; Lingqi Li; Haoran Li; Chang Liu; Ya Deng; Zi Wu; Yang Li (Journal of Hydrology, 2024)

Effects of microplastics on sedimentary greenhouse gas emissions and underlying microbiome-mediated mechanisms: A comparison of sediments from distinct altitudes - Meiling Yi; Jingnan Liu; Maosen Ma; Sibo Zhang; Xin Chen; Xinghui Xia; Yang Li (Journal of Hazardous Materials, 2024)

A novel multi-level reverse logistics network design optimization model for waste batteries considering facility technology types - Meiling He; Qipeng Li; Xiaohui Wu; Xun Han (Journal of Cleaner Production, 2024)

Acidic electrolyzed-oxidizing water treatment mitigated the disease progression in Phomopsis longanae Chi-infected longans by modulating ROS and membrane lipid metabolism - Meiling Li; Hetong Lin; Chao Wang; Yazhen Chen; Mengshi Lin; Yen-Con Hung; Yifen Lin; Zhongqi Fan; Hui Wang; Yihui Chen (Food Chemistry, 2024)

The immune function of heme oxygenase-1 (HO-1) from Nile tilapia (Oreochromis niloticus) in response to bacterial infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Nitric Oxide Promotes Adventitious Rooting in Cucumber Under Drought Stress Through Regulating Ascorbate Glutathione Cycle and Protein S-Nitrosylation - Xuemei Hou; Yuanyuan Dan; Nana Qi; Meiling Zhang; Changxia Li; Yihua Li; Yandong Yao; Weibiao Liao (Journal of Plant Growth Regulation, 2024)

A new method of alkalinity remediation for Cd-contaminated groundwater by PAAS-modified MgCO3/Mg(OH)2 colloid - Bowen Li; Meiling Tang; Peng Wang; Shibin Liu; Meng Yao; Jun Dong (Chemosphere, 2024)

The role of cyclin-dependent kinase inhibitor 3 in the proliferation and migration of renal cell carcinoma - Chenbo Ni; Zhisheng Guo; Hengtao Bu; Xusong Zhao; Meiling Bao; Lei Ding; Chao Liang; Qingsheng Tang; Jie Li (Chemico-Biological Interactions, 2024)

Calcium polypeptide mitigates Cd toxicity in rice via reducing oxidative stress and regulating pectin modification - Hongbing Chen; Xiaojun Tang; Tiejun Wang; Weifang Liao; Zhixian Wu; Meiling Wu; Zhihao Song; Yadong Li; Pan Luo (Plant Cell Reports, 2024)

MXene-based composite aerogels with bifunctional ferrous ions for the efficient degradation of phenol from wastewater - Gaoyuan Li; Weifeng Liu; Shaojun Gao; Huayu Lu; Dongju Fu; Meiling Wang; Xuguang Liu (Chemosphere, 2024)

Microbial role in enhancing transfer of straw-derived nitrogen to wheat under nitrogen fertilization - Shuyu Huang; Xue Gao; Li Zeng; Meiling Zhang; Liyu Zhang; Shiyu Wang; Yuanzheng Zhao; Wei Zhou; Chao Ai (Soil and Tillage Research, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Novel superhydrophobic sponge with flower-like architecture for oily emulsion separation and organic pollutants photodegradation - Jinyue Yang; Zhanjian Liu; Jing Jing; Xiguang Zhang; Yuxin Fu; Meiling Li; Huaiyuan Wang (Journal of Environmental Chemical Engineering, 2024)

Plio-Pleistocene drainage reorganization in the middle Yellow River of China, revealed by provenance and paleocurrent analysis of fluvial sediments - Menghao Li; Zhenbo Hu; Ping Wang; Baotian Pan; David Bridgland; Qinhong Mo; Xiaohua Li; Zijuan Dong; Meiling Zhong; Renzhe Pan; Ningyi Li (Geomorphology, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Seasonal changes in hepatic lipid metabolism and apoptosis in Chinese soft-shelled turtle (Pelodiscus sinensis) - Xiaoqi Ai; Rui Lin; Zeeshan Ali; Qingjun Zhu; Li Ding; Haitao Shi; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Validation of endogenous U6 promoters for expanding the CRISPR toolbox in Nicotiana tabacum - Pan Luo; Siyuan Li; Lulu Li; Yanyan Li; Ying Qiao; Xianzhi Wu; Meiling Wu; Zhihao Song; Yong Yang; Ji Feng; Xingchun Tang (In Vitro Cellular & Developmental Biology - Plant, 2024)

A jellyfish robot based on two-bar and four-spring tensegrity structures - Jianwei Sun; Changjian Li; Meiling Zhang; Lu Shen; Siyang Gao (Ocean Engineering, 2024)

Preparation, characterization and in vitro digestion of jujube polysaccharide microcapsules - Qingyi Li; Meiling Liu; Mengjun Liu; Huiqiang Wang; Zhihui Zhao (Food and Bioproducts Processing, 2024)

Embryonic development and transcriptomic analysis in red-eared slider Trachemys scripta elegans under salinity stress - Jing Lin; Yuchen Kong; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

The short-term effect of simulated acid rain and nitrogen deposition on the soil microbial functional profile targeting C, N, and P cycling - Chong Li; Yong Ding; Shuifeng Zhang; Meiling Chen; Yuhao Wang; Zhaohui Jia; Shilin Ma; Jinchi Zhang; Xin Liu (Applied Soil Ecology, 2024)

Comparative toxic effect of ammonia exposure on Mauremys sinensis and invasive species Trachemys scripta elegans - Li Ding; Zubin Huang; Lingyue Liang; Haitao Shi; Zhenhua Fang; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Synchronized achieving amount reduction and efficiency increase of lithium salt-type additive by alternating current pulse discharge technology - Shiyou Li; Yulong Zhang; Shumin Wu; Yin Quan; Meiling Wu; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2024)

Vertical variations of bacteriohopanepolyols near the Changjiang Estuary waters: Implications for marine hypoxia and bacterial activities - Meiling Yin; Liqin Duan; Jinming Song; Jiawei Kan; Huamao Yuan; Xuegang Li; Yingxia Wang (Chemical Geology, 2024)

Utilizing different types of biomass materials to modify steel slag for the preparation of composite materials used in the adsorption and solidification of Pb in solutions and soil - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Fanmin Zhu; Zhanbin Huang (Science of The Total Environment, 2024)

A novel method to advance the brGDGTs-based paleoclimate reconstruction applicable to different terrestrial environments - Liping Tian; Mengyuan Wang; Cong Chen; Xiao Zhang; Zhuo Zheng; Meiling Man; Kangyou Huang; Li Li; Guodong Jia (Quaternary Science Reviews, 2024)

Effects of butyl paraben on behavior and molecular mechanism of Chinese striped-necked turtle (Mauremys sinensis) - Xia Wu; Ijaz Khan; Xiaoqi Ai; Jiliang Zhang; Haitao Shi; Ding Li; Meiling Hong (Aquatic Toxicology, 2024)

Increased black carbon (soot) accumulation during the Anthropocene in a less-developed region of Xinjiang, northwestern China - Dewen Lei; Yongming Han; Changlin Zhan; Chong Wei; Yalan Tang; Meiling Guo; Jianing Zhang; Jingyu Li (Anthropocene, 2024)

Chemical features and biological functions of water-insoluble dietary fiber in plant-based foods - Meiling Tian; SolJu Pak; Chen Ma; Lingjun Ma; Kannan R. R. Rengasamy; Jianbo Xiao; Xiaosong Hu; Daotong Li; Fang Chen (Critical Reviews in Food Science and Nutrition, 2024)

Stepwise degradation of organic matters driven by microbial interactions in China΄s coastal wetlands: Evidence from carbon isotope analysis - Meiling Yang; Na Liu; Baoli Wang; Yajun Li; Wanzhu Li; Xinjie Shi; Xinrui Yue; Cong-Qiang Liu (Water Research, 2024)

Shaking table tests of a switching power cabinet considering physical damage and functionality loss - Haopeng Zuo; Guoliang Sun; Pengbo Zhang; Meiling Wang; Jichao Li; Qingxue Shang; Tao Wang (Soil Dynamics and Earthquake Engineering, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Unraveling seasonal shifts in microbial and geochemical mediated arsenic mobilization at the estuarine sediment-water interface under redox changes - Liqin Duan; Jinming Song; Yuting Zhang; Meiling Yin; Huamao Yuan; Xuegang Li (Science of The Total Environment, 2024)

Calcium isotopic compositions of eclogite melts and negligible modification during reaction with lithospheric mantle - Zongqi Zou; Zaicong Wang; Xiao-Jun Wang; Yi-Gang Xu; Li-Hui Chen; Meiling Wang; Lanping Feng; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

Molecular characteristics and functional analysis of non-specific cytotoxic cell receptor (NCCRP1) in golden pompano (Trachinotus ovatus) - Meiling Huang; Zhiqiang Zhang; Xing Li; Jiamin Feng; Yongxiong Huang; Amoah Kwaku; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Metagenomic binning analyses of swine manure composting reveal mechanism of nitrogen cycle amendment using kaolin - Huakang Li; Zixuan Zhao; Meiling Shi; Bin Luo; Guangdong Wang; Xiaojuan Wang; Jie Gu; Zilin Song; Yifan Sun; Li Zhang; Jia Wang (Bioresource Technology, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

Evolution of sustainability and its driving characteristics in typical energy-rich counties in underdeveloped Northwest China - Honghua Li; Xingang Fan; Meiling Yang; Xueli Chen; Manman Zhao (Environment, Development and Sustainability, 2024)

The role of energy transport system in pericarp browning of harvested longan fruit - Meiling Li; Hetong Lin; Yazhen Chen; Yihui Chen; Yifen Lin; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2024)

A Fe-Ni-MOF-74@bamboo photothermal evaporator for efficient solar steam generation - Yiduo Chen; Dongxu Gu; Yujuan Zhao; Chaowei Zhang; Meiling Li; Qi Zhou; Yonghui Lin; Yaru Gong; Zhongmin Su; Weiting Yang (Desalination, 2024)

Amino-functionalized nanocellulose aerogels for the superior adsorption of CO2 and separation of CO2/CH4 mixture gas - Wenkai Zhu; Meiling Chen; Jieun Jang; Minsu Han; Yeonggyun Moon; Junghwan Kim; Jungmok You; Song Li; Teahoon Park; Jeonghun Kim (Carbohydrate Polymers, 2024)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Predicting and extracting thermal behavior rules of hydronic thermal barrier with interpretable ensemble learning in the heating season - Juanli Guo; Zhoupeng Wang; Yongyun Jin; Meiling Li; Qingwei Chen (Energy and Buildings, 2023)

Scalable fabrication of a robust asymmetric superwetting Janus mesh by facile spray-coating for oil–water emulsions separation - Jing Jing; Zhanjian Liu; Xiguang Zhang; Jinyue Yang; Meiling Li; Ruixia Yuan; Guolin Jing; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Progress on the roles of zinc in sperm cryopreservation - Yuanyou Li; Shaoyu Qin; Wenfei Cui; Fan Zhao; Meiling He; Zhongliang Jiang (Theriogenology, 2023)

Experimental and mechanistic study on the removal of lead from solution by sulfuric acid modified steel slag adsorbent - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Apolipoprotein Eb (On-ApoEb) protects Oreochromis niloticus against Streptococcus agalactiae infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Interleukin-8 involved in Nile Tilapia (Oreochromis niloticus) against bacterial infection - Xing Li; Baijian Jiang; Zhiqiang Zhang; Meiling Huang; Jiamin Feng; Yongxiong Huang; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

Baicalein ameliorates polymyxin B-induced acute renal injury by inhibiting ferroptosis via regulation of SIRT1/p53 acetylation - Meiling Yu; Hongyu Li; Boying Wang; Zhenxiang Wu; Sheng Wu; Guojun Jiang; Huaxue Wang; Yingying Huang (Chemico-Biological Interactions, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Involvement of CD27 in innate and adaptive immunities of Nile tilapia (Oreochromis niloticus) - Baijian Jiang; Qi Li; Zhiqiang Zhang; Yongxiong Huang; Yiqin Wu; Xing Li; Meiling Huang; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Ag2S QDs integration with MnO2 nanosheets for the sensitive detection of Cr (VI) via the redox reaction induced photoelectrochemical variation - Lili Zhao; Haoyu Chen; Ying Tang; Peipei Li; Xiaohua Zhu; Jingyi Liu; Meiling Liu; Youyu Zhang; Shouzhuo Yao (Analytica Chimica Acta, 2023)

The positive effects of mineral-solubilizing microbial inoculants on asymbiotic nitrogen fixation of abandoned mine soils are driven by keystone phylotype - Chong Li; Zhaohui Jia; Shuifeng Zhang; Tao Li; Shilin Ma; Xuefei Cheng; Meiling Chen; Hui Nie; Lu Zhai; Bo Zhang; Xin Liu; Jinchi Zhang; et al. (Science of The Total Environment, 2023)

Decomplexation of Ni-EDTA by thermally activated persulfate: Efficiency and mechanism - Xinkai Yuan; Wei Xiong; Yanhua Peng; Bo Li; Jianzhi Zhang; Meiling Chen; Xiuqin Xiong; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Journal of Water Process Engineering, 2023)

Atomically dispersed metal catalysts towards nitrogen reduction for Ammonia: From homogeneous to heterogeneous - Di Yang; Jinsheng Li; Meiling Xiao; Changpeng Liu; Wei Xing; Jianbing Zhu (Chemical Engineering Journal, 2023)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

Channel migration in the northeastern margin of the Tibetan Plateau and its implication for fluvial response to the interaction between rapid tectonic activity, climatic fluctuation and human influence - Baotian Pan; Xiaohua Li; Zhenbo Hu; David Bridgland; Qinhong Mo; Zijuan Dong; Menghao Li; Yanan Yang; Rob Westaway; Guanghui Dong; Shanjia Zhang; Meiling Zhong (Quaternary Science Reviews, 2023)

Application of interaction models in predicting the simultaneous growth of Staphylococcus aureus and different concentrations of background microbiota in Chinese-style braised beef - Chuansong Cheng; Binxiong Liu; Meiling Tian; Ting Fang; Changcheng Li (Meat Science, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Ferroptosis is involved in polymyxin B-induced acute kidney injury via activation of p53 - Hongyu Li; Boying Wang; Sheng Wu; Shuying Dong; Guojun Jiang; Yingying Huang; Xuhui Tong; Meiling Yu (Chemico-Biological Interactions, 2023)

Seasonal spermatogenesis in the red-eared slider (Trachemys scripta elegans): The roles of GnRH, actin cytoskeleton, and MAPK - Na Li; Wenzhuo Rao; Shiyu Dai; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Animal Reproduction Science, 2023)

Catalytic destruction of chlorobenzene over K-OMS-2: Inhibition of high toxic byproducts via phosphate modification - Yunpeng Long; Jiajia Liu; Meiling Chen; Renna Li; Xiaole Weng; Zhongbiao Wu (Journal of Environmental Sciences, 2023)

Subducted carbonates not required: Deep mantle melting explains stable Ca isotopes in kimberlite magmas - Michael A. Antonelli; Andrea Giuliani; Zaicong Wang; Meiling Wang; Lian Zhou; Lanping Feng; Ming Li; Zhaofeng Zhang; Fang Liu; Russell N. Drysdale (Geochimica et Cosmochimica Acta, 2023)

Involvement of a receptor-like kinase complex of FvFLS2 and FvBAK1 in brassinosteroids-induced immunity in postharvest strawberry fruit - Chunhong Li; Kaituo Wang; Meiling Tan; Changyi Lei; Shifeng Cao (Postharvest Biology and Technology, 2023)

Electrooxidation of methane to acetic acid over ZnO nanosheets: Defect-sites engineering - Mingming Luo; Jiayao Li; Meiling Wang; Yongqing Ma; Ganhong Zheng; Min Wang; Yitong Zhou (Journal of Environmental Chemical Engineering, 2023)

A Quad-Functional On-demand released nanomissile achieves cascade amplification therapy of Triple-Negative breast cancer through reversing multiple resistance - Yan Wang; Xianzhou Huang; Shunyao Zhu; Lu Li; Jin Yang; Jie Li; Li Wang; Shuang Ma; Meiling Shen; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2023)

Profiles and key drivers of bacteria/phage co-mediated antibiotic resistance genes during swine manure composting amended with humic acid - Meiling Shi; Zixuan Zhao; Xiaojuan Wang; Huakang Li; Jie Gu; Zilin Song; Ting Hu; Yifan Sun; Han Wang (Bioresource Technology, 2023)

The infertile individual analysis based on whole-exome sequencing in chinese multi-ethnic groups - Qiongzhen Zhao; Yanqi Li; Qi Liang; Jie Zhao; Kai Kang; Meiling Hou; Xin Zhang; Renqian Du; Lingyin Kong; Bo Liang; Weidong Huang (Genes & Genomics, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Acidic electrolyzed water treatment suppresses Phomopsis longanae Chi-induced the decreased storability and quality properties of fresh longans through modulating energy metabolism - Meiling Li; Qin Lin; Yazhen Chen; Yihui Chen; Mengshi Lin; Yen-Con Hung; Hetong Lin (Food Chemistry, 2023)

North-south differences in hypoxia and nitrogen cycle of the East China Sea over the last century indicated by sedimentary bacteriohopanepolyols - Meiling Yin; Jinming Song; Liqin Duan; Huamao Yuan; Xuegang Li; Quancai Peng (Chemical Geology, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

Intermetallic niobium boride toward efficient adsorption and catalysis of polysulfides in Lithium-Sulfur batteries - Li He; Yingjie Cheng; Qiuju Li; Hainan Zhao; Meiling Wang; Xuejian Shi; Xiaoxin Zou; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

Rapamycin ameliorates brain damage and maintains mitochondrial dynamic balance in diabetic rats subjected to middle cerebral artery occlusion - Changchun Hei; Yujia Zhou; Chenyang Zhang; Furong Gao; Meiling Cao; Shilin Yuan; Yixin Qin; P. Andy Li; Xiao Yang (Metabolic Brain Disease, 2023)

Simultaneous determination of 13 paralytic shellfish toxins and tetrodotoxin in marine shellfish by porous graphitic carbon solid-phase extraction and hydrophilic interaction chromatography-tandem mass spectrometry - Peizhen Li; Rongmao Lu; Jie Zhu; Qingqing Ke; Dingnan Wang; Yang Wang; Chen Zhang; Xinyue Lu; Miaolong Zhao; Zhang Wang; Lingling Pan; Meiling Zhang; et al. (Food Additives & Contaminants: Part A, 2023)

High-throughput sequencing reveals tuber mustard genes responsive to Plasmodiophora brassicae in the early stage of infection - Zhaoming Cai; Meiqin Xiang; Jing Tan; Chunhong Cheng; Ying Liu; Jiayu Shi; Meiling Shi; Jin Li; Diandong Wang (Physiological and Molecular Plant Pathology, 2023)

Diesel removal and recovery from heavily diesel-contaminated soil based on three-liquid-phase equilibria of diesel + 2-butyloxyethanol + water - Zhijie Shang; Pan Xu; Zhenyu Ke; Meiling Yao; Xinxue Li (Journal of Hazardous Materials, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

Long-term effect of submicronic particulate matter (PM1) and intermodal particulate matter (PM1-2.5) on incident dyslipidemia in China: A nationwide 5-year cohort study - Meiling Hu; Jing Wei; Yaoyu Hu; Xiuhua Guo; Zhiwei Li; Yuhong Liu; Shuting Li; Yongxi Xue; Yuan Li; Mengmeng Liu; Lei Wang; Xiangtong Liu (Environmental Research, 2023)

Effect of ammonia stress on AMPK regulating-carbohydrate and lipid metabolism in Chinese striped-neck turtle (Mauremys sinensis) - Ijaz Khan; Yingnan Lu; Na Li; Haitao Shi; Li Ding; Meiling Hong; Zhenhua Fang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

A highly-stretchable and adhesive hydrogel for noninvasive joint wound closure driven by hydrogen bonds - Hongsheng Liu; Xiaole Hu; Wen Li; Meiling Zhu; Jinhuan Tian; Lihua Li; Binghong Luo; Changren Zhou; Lu Lu (Chemical Engineering Journal, 2023)

Eco-friendly waterborne superhydrophobic/superoleophilic FEVE composite coating with prolonged mechanochemical and anti-scaling properties - Zhanjian Liu; Lina Ren; Baoshuang Zhang; Jing Jing; Xiguang Zhang; Meiling Li; Yuxin Fu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

A colloidal aqueous electrolyte modulated by oleic acid for durable zinc metal anode - Meiling Wang; Xiaoyu Wu; Di Yang; Hainan Zhao; Li He; Jiaran Su; Xu Zhang; Xiuxiu Yin; Kangning Zhao; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

Corrigendum to “Dynamic characteristics and adaptive design methods of enclosed courtyard: A case study of a single-story courtyard dwelling in China” [Build. Environ. 223 (2022) 109445] - Meiling Li; Yongyun Jin; Juanli Guo (Building and Environment, 2023)

SnoRNP is essential for thermospermine-mediated development in Arabidopsis thaliana - Xilong Li; Zongyun Yan; Meiling Zhang; Jiayin Wang; Peiyong Xin; Shujing Cheng; Liquan Kou; Xiaoting Zhang; Songlin Wu; Jinfang Chu; Chengqi Yi; Keqiong Ye; et al. (Science China Life Sciences, 2023)

Nonconservative behavior of dissolved molybdenum and its potential role in nitrogen cycling in the Bohai and Yellow Seas - Jinqi Fan; Liqin Duan; Meiling Yin; Huamao Yuan; Xuegang Li (Frontiers in Marine Science, 2022)
Molybdenum plays an important role in marine biological activity, especially in nitrogen cycling as a cofactor for N 2 fixation and nitrate reductase. However, the dissolved Mo (dMo) behavior and its interaction with N cycling in the coastal waters is still unclear. In this study, the dMo concentrations and parameters related to Mo distribution and N cycling in surface and bottom seawaters of the Bohai (BS) and Yellow Seas (YS) were examined. The results showed that dMo concentrations ranged from 36.4 nmol L -1 to 125.0 nmol L -1 , most of which deviated significantly from the conservative line, indicating nonconservative behavior of Mo relative to salinity. The highest dMo concentrations occurring in 36°N section of north of the South YS (SYS), were close to conservative value (105 nmol L -1 ). Significant depletion up to 40-50 nmol L -1 of dMo mainly appeared in the BS, NYS and south of the SYS, suggesting the possible removal of dMo by biological utilization and particle adsorption. Particularly, the increasing dMo concentrations away the Yellow River estuary indicated that freshwater dilution was one of reasons for dMo distributions in the BS. The similar spatial distribution of dMo and dissolved Mn concentrations suggested the possible scavenging by MnO x phases for Mo removal. The negative correlation between dMo and chlorophyll- a (Chl- a ) concentrations in surface seawaters suggested that biological uptake was involved in dMo removal. The depleted dMo in most of sites corresponded with the higher nitrite concentrations, implying the possible involvement of nitrate reduction process. Although the highest N 2 fixation rates and relative abundances of cyanobacteria appeared in 36°N section, corresponding with the conservative dMo, suggesting that Mo may play a minor role in N 2 fixation process there. The ten-folds of relative abundance of bacteria with nitrate reduction function than that with N 2 fixation function suggested that dMo seems to play more important role in nitration reduction than nitrogen fixation in the BS and YS.

Integrated eco-physiological, biochemical, and molecular biological analyses of selenium fortification mechanism in alfalfa - Qingdong Wang; Jinke Hu; Huafeng Hu; Yan Li; Meiling Xiang; Dezhen Wang (Planta, 2022)

Plant Growth Regulators Enhance Saline–Alkali Tolerance by Upregulating the Levels of Antioxidants and Osmolytes in Soybean Seedlings - Minglong Yu; Qiong Wu; Dianfeng Zheng; Naijie Feng; Xilong Liang; Meiling Liu; Yao Li; Baomin Mou (Journal of Plant Growth Regulation, 2022)

LncRNA Tug1 Contributes Post-stroke NLRP3 Inflammasome-Dependent Pyroptosis via miR-145a-5p/Tlr4 Axis - Meiling Yao; Ying Luo; Hongjie Li; Songjie Liao; Jian Yu (Molecular Neurobiology, 2022)

Can urban rail transit reduce haze pollution? A spatial difference-in-differences approach - Yumei Lin; Meiling Li; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Meiling Ge; Jing Mo; Jack Chi-Ho Ip; Yixuan Li; Wenge Shi; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers ( 18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.

Effects of Microplastics on Higher Plants: A Review - Jia Li; Songguo Yu; Yufei Yu; Meiling Xu (Bulletin of Environmental Contamination and Toxicology, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Does lower regional density result in less CO2 emission per capita? - Yumei Lin; Junpei Huang; Meiling Li; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Effects of Epichloë endophytes on litter decomposition--depending on different host species - Meiling Song; Yuqin Wang; Hongsheng Wang; Gensheng Bao; Xiuzhang Li (Plant and Soil, 2022)

Development and characterization of novel chloroplast microsatellite markers for Cryptomeria japonica var. sinensis (Cupressaceae) and their cross-species amplification - Minqiu Wang; Meiling Yuan; Xinyu Li; Xingtong Wu; Saneyoshi Ueno; Mengying Cai; Yoshihiko Tsumura; Yafeng Wen (Biologia, 2022)

Role of gibberellin and its three GID1 receptors in Jasminum sambac stem elongation and flowering - Hongliang Zhang; Wei Wang; Jinfeng Huang; Yuting Wang; Li Hu; Yuan Yuan; Meiling Lyu; Binghua Wu (Planta, 2022)

Aggregate sizes regulate the microbial community patterns in sandy soil profile - Yifei Sun; Meiling Sun; Guowei Chen; Xin Chen; Baoguo Li; Gang Wang (Soil Ecology Letters, 2021)

Quality Study of the Preparation of Virgin Brown Sugar Powder by Vacuum Drying - Yuchao Dai; Mingxing Li; Meiling Li; Zhuolin Wang; Jie Lu; Yiyang Zhou; Wenping Meng; Shufang Chen; Qingtao Li (Sugar Tech, 2021)

A new parametric segmentation method based on sandy mudstone SEM images - Meiling Zhou; Jianlin Li; Weijie Xu; Feng Xu; Eleyas Assefa; Huafeng Deng (Arabian Journal of Geosciences, 2021)

The role of macrophage scavenger receptor 1 (Msr1) in prion pathogenesis - Bei Li; Meiling Chen; Adriano Aguzzi; Caihong Zhu (Journal of Molecular Medicine, 2021)
The progression of prion diseases is accompanied by the accumulation of prions in the brain. Ablation of microglia enhances prion accumulation and accelerates disease progression, suggesting that microglia play a neuroprotective role by clearing prions. However, the mechanisms underlying the phagocytosis and clearance of prion are largely unknown. The macrophage scavenger receptor 1 (Msr1) is an important phagocytic receptor expressed by microglia in the brain and is involved in the uptake and clearance of soluble amyloid-β. We therefore asked whether Msr1 might play a role in prion clearance and assessed the scavenger function of Msr1 in prion pathogenesis. We found that Msr1 expression was upregulated in prion-infected mouse brains. However, Msr1 deficiency did not change prion disease progression or lesion patterns. Prion deposition in Msr1 deficient mice was similar to their wild-type littermates. In addition, prion-induced neuroinflammation was not affected by Msr1 ablation. We conclude that Msr1 does not play a major role in prion pathogenesis. Key messages Msr1 expression is upregulated in prion-infected mouse brains at the terminal stage Msr1 deficiency does not affect prion disease progression Msr1 does not play a major role in prion clearance or prion pathogenesis Microglia-mediated phagocytosis and clearance of Aβ and prion may adopt distinct molecular pathways

Pigment profile and gene analysis revealed the reasons of petal color difference of crabapples - Ting Shen; Meiling Han; Qianrui Liu; Chen Yang; Jiaxin Meng; Houhua Li (Brazilian Journal of Botany, 2021)

First detection and genetic characterization of equid herpesvirus 2, 4, and 5 in China - Jinxin Xie; Panpan Tong; Lei Zhang; Meiling Ren; Xiaozhen Song; Chenyang Jia; Nuerlan Palidan; Li Zhang; Ling Kuang (Archives of Virology, 2021)

Proteomic Analysis of Serum Differentially Expressed Proteins Between Allergic Bronchopulmonary Aspergillosis and Asthma - Hui Cai; Diquan Shuai; Xiaomin Xue; Yuqing Mo; Xixi Song; Ling Ye; Shuiming Li; Daiwei Wang; Yun Wang; Meiling Jin (Mycopathologia, 2021)

The Effect of Composting on the Multiple Heavy Metals in the River Sediment Investigated by Multivariate Analysis - Yaoning Chen; Yanrong Chen; Yuanping Li; Yihuan Liu; Daoli Zhang; Yanxin Wu; Hui Li; Fangting Xu; Meiling Li (Water, Air, & Soil Pollution, 2021)

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)

A tale of two cities: different urban heat mitigation efficacy with the same strategies - Meiling Gao; Fei Chen; Huanfeng Shen; Huifang Li (Theoretical and Applied Climatology, 2020)

Functional wastepaper-montmorillonite composite aerogel for Cd2+ adsorption - Yaoning Chen; Yihuan Liu; Yuanping Li; Li Zhao; Yanrong Chen; Hui Li; Yuqing Liu; Linshenzhang Li; Fangting Xu; Meiling Li (Environmental Science and Pollution Research, 2020)

MicroRNA-375 overexpression disrupts cardiac development of Zebrafish (Danio rerio) by targeting notch2 - Sisi Zhuang; Yanrong Fu; Jingyun Li; Mengmeng Li; Xiaoshan Hu; Jingai Zhu; Meiling Tong (Protoplasma, 2020)

The Role of Arachidonic Acid Metabolism in Myocardial Ischemia–Reperfusion Injury - Changjiang Zhang; Meiling He; Lihua Ni; Ke He; Ke Su; Yinzhi Deng; Yuanhong Li; Hao Xia (Cell Biochemistry and Biophysics, 2020)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Metanephric mesenchyme-derived Foxd1+ mesangial precursor cells alleviate mesangial proliferative glomerulonephritis - Meiling Jin; Zhong Yin; Kai Wei; Yuansheng Xie; Xueyuan Bai; Bo Fu; Zhe Feng; Qinggang Li; Xiangmei Chen (Journal of Molecular Medicine, 2019)

Gut Microbiota and its Modulation for Healthy Farming of Pacific White Shrimp Litopenaeus vannamei - Erchao Li; Chang Xu; Xiaodan Wang; Shifeng Wang; Qun Zhao; Meiling Zhang; Jian G. Qin; Liqiao Chen (Reviews in Fisheries Science & Aquaculture, 2018)

Important interaction of chemicals, microbial biomass and dissolved substrates in the diel hysteresis loop of soil heterotrophic respiration - Qing Wang; Nianpeng He; Yuan Liu; Meiling Li; Li Xu; Xuhui Zhou (Plant and Soil, 2018)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Design and analysis of a generalized DLL/FLL discriminator for GPS receivers - Yafeng Li; Meiling Wang; Nagaraj C. Shivaramaiah (GPS Solutions, 2018)

Characterization of a novel dsRNA mycovirus isolated from strain A105 of Rhizoctonia solani AG-1 IA - Meiling Zhang; Li Zheng; Chen Liu; Canwei Shu; Erxun Zhou (Archives of Virology, 2018)

Multiple timescale analysis of the urban heat island effect based on the Community Land Model: a case study of the city of Xi’an, China - Meiling Gao; Huanfeng Shen; Xujun Han; Huifang Li; Liangpei Zhang (Environmental Monitoring and Assessment, 2018)

Latitudinal patterns and influencing factors of soil humic carbon fractions from tropical to temperate forests - Li Xu; Chunyan Wang; Jianxing Zhu; Yang Gao; Meiling Li; Yuliang Lv; Guirui Yu; Nianpeng He (Journal of Geographical Sciences, 2018)

Triassic ore-bearing and barren porphyries in the Zhongdian Arc of SW China: implications for the subduction of the Palaeo-Tethys Ocean - Peng Wang; Guochen Dong; M. Santosh; Xuefeng Li; Meiling Dong (International Geology Review, 2017)

Molecular cloning and expression analysis of major intrinsic protein gene in Chlamydomonas sp. ICE-L from Antarctica - Lulu Li; Meiling An; Changfeng Qu; Zhou Zheng; Yibin Wang; Fangming Liu; Yingying He; Xiaodong He; Jinlai Miao (Extremophiles, 2017)

A glucuronokinase gene in Arabidopsis, AtGlcAK, is involved in drought tolerance by modulating sugar metabolism - Wenjun Xiao; Shuai Hu; Xiaoxun Zhou; Runyu Yao; Jingru Luo; Congying Yuan; Hongping Chang; Cheng Zhang; Ji Huang; Jinyan Li; Shucan Liu; Meiling Li; et al. (Plant Molecular Biology Reporter, 2017)

Comparative genomic analysis of three white spot syndrome virus isolates of different virulence - Fang Li; Meiling Gao; Limei Xu; Feng Yang (Virus Genes, 2017)

Allelism analysis of BrRfp locus in different restorer lines and map-based cloning of a fertility restorer gene, BrRfp1, for pol CMS in Chinese cabbage (Brassica rapa L.) - Huamin Zhang; Junqing Wu; Zihui Dai; Meiling Qin; Lingyu Hao; Yanjing Ren; Qingfei Li; Lugang Zhang (Theoretical and Applied Genetics, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

The chlorophyll-deficient golden leaf mutation in cucumber is due to a single nucleotide substitution in CsChlI for magnesium chelatase I subunit - Meiling Gao; Liangliang Hu; Yuhong Li; Yiqun Weng (Theoretical and Applied Genetics, 2016)

Abnormal Functional Connectivity Density in Post-traumatic Stress Disorder - Youxue Zhang; Bing Xie; Heng Chen; Meiling Li; Feng Liu; Huafu Chen (Brain Topography, 2016)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)

An asexual Epichloë endophyte modifies the nutrient stoichiometry of wild barley (Hordeum brevisubulatum) under salt stress - Meiling Song; Qing Chai; Xiuzhang Li; Xiang Yao; Chunjie Li; Michael J. Christensen; Zhibiao Nan (Plant and Soil, 2015)

Cloning and structure of a histocompatibility class IIA gene (Lelo-DAA) in Chinese longsnout catfish (Leiocassis longirostris) - Tong Shen; Xiaoshun He; Meiling Lei; Jingru Wang; Xiuming Li; Jianming Li (Genes & Genomics, 2014)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Fimbria–fornix (FF)-transected hippocampal extracts induce the activation of astrocytes in vitro - Linqing Zou; Haoming Li; Guohua Jin; Meiling Tian; Jianbing Qin; Heyan Zhao (In Vitro Cellular & Developmental Biology - Animal, 2014)

The complete genomic sequence of a novel mycovirus from Rhizoctonia solani AG-1 IA strain B275 - Li Zheng; Huiquan Liu; Meiling Zhang; Xiong Cao; Erxun Zhou (Archives of Virology, 2013)

Resveratrol protects against arsenic trioxide-induced nephrotoxicity by facilitating arsenic metabolism and decreasing oxidative stress - Meiling Yu; Jiangdong Xue; Yijing Li; Weiqian Zhang; Dexing Ma; Lian Liu; Zhigang Zhang (Archives of Toxicology, 2013)

Steroid 5-alpha-reductase type 2 (SRD5A2) V89L and A49T polymorphisms and sporadic prostate cancer risk: a meta-analysis - Qiaoxin Li; Yao Zhu; Jing He; Mengyun Wang; Meiling Zhu; Tingyan Shi; Lixin Qiu; Dingwei Ye; Qingyi Wei (Molecular Biology Reports, 2013)

LIM-homeobox gene Lhx8 promote the differentiation of hippocampal newborn neurons into cholinergic neurons in vitro - Peipei Zhu; Haoming Li; Guohua Jin; Meiling Tian; Xuefeng Tan; Jinhong Shi; Linqing Zou; Jianbing Qin (In Vitro Cellular & Developmental Biology - Animal, 2013)

Lhx8 promote differentiation of hippocampal neural stem/progenitor cells into cholinergic neurons in vitro - Jinhong Shi; Haoming Li; Guohua Jin; Peipei Zhu; Meiling Tian; Jianbing Qin; Xuefeng Tan; Shuqing Zhao; Fuyu Wang; Yurong Hua; Yong Xiao (In Vitro Cellular & Developmental Biology - Animal, 2012)

In vitro evaluation of a mammary gland specific expression vector encoding recombinant human lysozyme for development of transgenic dairy goat embryos - Tao Gui; Meiling Zhang; Jianwen Chen; Yuanliang Zhang; Naru Zhou; Yu Zhang; Jia Tao; Liucai Sui; Yunsheng Li; Ya Liu; Xiaorong Zhang; Yunhai Zhang (Biotechnology Letters, 2012)

Characterization and identification of Sox2+ radial glia cells derived from rat embryonic cerebral cortex - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Jinhong Shi; Weiwei Yang; Xuefeng Tan; Xinhua Zhang; Linqing Zou (Histochemistry and Cell Biology, 2011)

Effect of trichostatin A and 5-Aza-2′-deoxycytidine on transgene reactivation and epigenetic modification in transgenic pig fibroblast cells - Qingran Kong; Meiling Wu; Zhenkun Wang; Xinmiao Zhang; Lu Li; Xiangyu Liu; Yanshuang Mu; Zhonghua Liu (Molecular and Cellular Biochemistry, 2011)

Generation and identification of rat fetal cerebral radial glia-like cells in vitro - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Xuefeng Tan; Xinhua Zhang; Weiwei Yang; Jinhong Shi; Linqing Zou (In Vitro Cellular & Developmental Biology - Animal, 2011)

Long-term cultured callus and the effect factor of high-frequency plantlet regeneration and somatic embryogenesis maintenance in Zoysia japonica - Li Liu; Xiaoli Fan; Junwei Zhang; Meiling Yan; Manzhu Bao (In Vitro Cellular & Developmental Biology - Plant, 2009)